Pemberdayaan Masyarakat Dalam Pengendalian Tekanan Darah Pada Nelayan Teluk Rhu, Rupat Utara - Zulkarnaini Zulkarnaini; Suyanto Suyanto; Thamrin Thamrin; Ariza Julia Paulina; Rosmayani Rosmayani; Riza Fitriana (PELANTAR PRESS, 2024)
Hypertension is one of the main health problems at risk of causing cardiovascular diseases, such as heart attack and stroke, which requires special attention in coastal areas, including Teluk Rhu Village, North Rupat Sub-district, Bengkalis Regency. Based on an initial survey, the incidence of hypertension in this village is quite high, especially among fishermen who have an irregular lifestyle and limited knowledge about the risks of hypertension. In order to overcome this problem, Community Service activities (PKM) were carried out on May 20, 2024 with the aim of increasing community knowledge and awareness about hypertension through counseling, health checks, and distribution of educational materials. This activity also involves students as facilitators and brings health services closer to people living in remote areas.The evaluation results showed that this program succeeded in increasing community knowledge about hypertension and its prevention measures. Of the 30 participants who took part in the blood pressure check, 10 of them were diagnosed with hypertension and given recommendations for treatment and regular check-ups. In addition, this activity also introduced technology in the form of educational media such as posters and videos to deepen the community's understanding of the symptoms and management of hypertension. Although the program has been running well, there is still a need to improve health facilities and early detection to expand the scope of education and treatment, especially for high-risk communities. With the establishment of a hypertension club and improved health services, it is hoped that the prevalence of hypertension can be reduced and the quality of life of the people of Teluk Rhu Village improved